Spectroscopic and DFT Studies of Distinct Anilines for Electronic and Optical Properties - Kumar, Ch. Ravi Shankar (New Trends in Physical Science Research Vol. 5, 2022)
Significant investigations of anilines used experimental and computational research like CNDO, MINDO, and PCILO to report biological activities such oxidation, polymerization, arylation, alkylation, protonation, and conformation for photophysical and electrochemical properties. These interactions nonetheless provide ample scope for determining physical, chemical, and electrooptical properties utilizing the electron density approach. The present work attributes family of anilines-aniline (AN), p-chloroaniline (CAN) and p-nitroaniline (NAN) with experimental studies like FTIR and FT Raman and Computational studies with GaussView4.1 package using B3LYP–basis set 6-311++(d,p) for electrooptical properties. Interpretation of experimental spectra of FTIR and FT Raman confirm the wave numbers are in specified range corresponding to functional group and fingerprint regions. In compared to infrared spectra, the intensity of the wave numbers in Raman spectra is found to be lower. For molecular characteristics, molecular structures are depicted using the molecular editor Avogadro. For optimal structures, computational analyses are carried out to ensure that calculated infrared and Raman spectra agree with experimental spectra. The dipole moment, EHomo, ELumo, energy gap, electrophilicity index, polarization, and first order hyperpolarizability are all determined by charge transfer interactions. NAN has a higher tendency in charge transfer interactions with a smaller energy gap, high polarizability, and first order Hyperpolarizability, allowing sophisticated optical materials and devices to be formed.